2009
DOI: 10.1111/j.1467-7652.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a KCS gene from Cardamine graeca and its heterologous expression in Brassica oilseeds to engineer high nervonic acid oils for potential medical and industrial use

Abstract: Database: The C. gracea KCS sequence information has been submitted to the EMBL ⁄ GenBank under accession number: bankit1110928.Keywords: 3-keto-acyl-CoA synthase, Cardamine graeca, Nervonic acid, Brassica carinata, Brassica napus, Arabidopsis thaliana, Health and Industry. SummaryNervonic acid 24:1 D15 (cis-tetracos-15-enoic acid) is a very long-chain monounsaturated fatty acid and exists in nature as an elongation product of oleic acid.There is an increasing interest in production of high nervonic acid oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 58 publications
2
93
0
Order By: Relevance
“…KCS is a component of the elongation complex responsible for the synthesis of very long chains of monounsaturated fatty acids (VLCMFA) in the seeds of plants [16]. The KCS gene showed an expression pattern of Category III, which was constitutively expressed throughout endosperm development (Figure 5H).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KCS is a component of the elongation complex responsible for the synthesis of very long chains of monounsaturated fatty acids (VLCMFA) in the seeds of plants [16]. The KCS gene showed an expression pattern of Category III, which was constitutively expressed throughout endosperm development (Figure 5H).…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (2009) produced transgenic Arabidopsis and Brassica Carinata plants that expressed Cardamine KCS gene. The seed-specific expression of the Cardamine KCS gene led to 55-fold and 15-fold increase in nervonic acid proportions in Arabidopsis and B. carinata seed oil, respectively [16]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have described the ability to increase total oil content of seeds by transgenic expression of DGAT1 and DGAT2 enzymes of plant and fungal origin (Jako et al ., 2001; Lardizabal et al ., 2008; Oakes et al ., 2011). Seed-specific overexpression of Arabidopsis DGAT1, for example, increased oil content by up to 15 and 46% in seeds of transgenic Brassica napus and Arabidopsis , respectively (Jako et al ., 2001; Sharma et al ., 2008; Taylor et al ., 2009). Small increases in oil content of maize and soybean seeds were conferred by expression of the fungus Umbelopsis ramanniana DGAT2 (Lardizabal et al ., 2008; Oakes et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable plants for such manipulation include Brassica species such as B. napus, B. juncea and B. rapa, Crambe species such as C. abyssinica and C. hispanica, and Limnanthes species such as L. alba alba and L. douglasii (meadowfoam). seed-specifi c reduction in Δ15 desaturase activity.In another recent development Taylor et al[238] have reported the signifi cant accumulation of the unusual VLCFA nervonic acid (C24:1Δ15) in Brassica oilseeds by metabolic engineering. Annual honesty (Lunaria annua…”
mentioning
confidence: 99%